Simulation study of orthogonal eddy current excitation technique for detection of multi-orientation slit - Mohd Mawardi, Saari; Nurul A’in, Nadzri; Mohd Aufa Hadi Putera, Zaini; Mohd Herwan, Sulaiman; Kiwa, Toshihiko (IEEE, 2024)
Identifying crack propagation direction and depth is crucial for steel structure safety. This study explores an orthogonal eddy current excitation technique for detecting multi-orientation slits in mild steels. Using 3-D finite element (FE) simulation, the normal magnetic response Bz distribution induced by orthogonal eddy current excitation is calculated. Two perpendicular inductor arrays mimic orthogonal eddy currents. Artificial vertical, horizontal, 45°, and cross slits on a 12-mm mild steel plate are modeled, and the normal magnetic response contributed by these slits is simulated. Findings show that the orthogonal eddy current excitation technique causes a change in the magnetic field distribution for all types of slits, indicating its ability to resolve any orientation of the slits. Both x- and y-differential signals exhibit similar sensitivity in detecting vertical and horizontal slits. In contrast to the real component of the differential signal, the imaginary components showed a higher normalized differential value due to slits, suggesting a higher detection sensitivity of the differential imaginary components. The orthogonal eddy current induction technique would be a preferable choice to be implemented in an ECT probe.